Results of simulation modeling of technical parameters of a multiservice network - Alevtina Aleksandrovna Muradova; Dilbar Turgunovna Normatova (Universitas Ahmad Dahlan, 2023)
In a scientific article, the authors presented the results of simulation modeling of the technical parameters of a multiservice network. As a model of a multiservice communication network for the computational experiment, the model proposed in the previous scientific publications of the author was chosen. The selected model uses the Laplase-Stilles transform. Simulation modeling was carried out using the technical parameters of the multiservice network’s availability factor and network load. Scientific results of experimental research work are given in the form of tables. Relations of the probability of betime servicing of an application on the load of a multiservice communication network for various availability factors and the probability of untimely service of an application on the availability factor for numerous network loadings are obtained. The character of the distribution of costs necessary for the implementation of solutions for different categories of technical operation is shown. Scientific research on determining the objective function’s minimum value is presented in graphs and diagrams. The results of simulation modeling of the technical parameters of multiservice networks are presented in the form of diagrams using the Matlab software environment.